Budgeting in small manufacturing firms in South Africa - J. C. Ford; M. Lurie (South African Journal of Business Management, 1989)
This paper reports on a general investigation into budgeting in small manufacturing firms in South Africa. The study was undertaken using 18 semi-formal interviews and 175 questionnaires addressed to the Chief Executive Officers (CEOs) of small manufacturing firms in six industry sectors in the greater Johannesburg region. The 63 usable responses (a response rate of 36%) were analysed using the SAS statistical package. Several results and conclusions were reached. A wide range of budgetary processes and procedures are used by small manufacturing firms. Budgeting is short-term, informal, simple and flexible, and is considered an essential element of management. There is room for much improvement in certain areas of budgeting. Although accounting reports are perceived to be adequate, CEOs may lack the necessary knowledge to develop more effective reporting systems. The degree of budgeting used is probably influenced by the nature of the business, and the background and training of the CEO. CEOs are completely involved in budgeting, but there is little participation by managers and staff. The major benefits of budgeting are perceived to be its use in planning and control, particularly of cash, and the major problems relate to the uncertainty of future conditions.
Keywords: 650